How to Document Ontology Design Patterns : Supporting Data Part 2 - Hammar, Karl (Jönköping University, 2016)
Survey data presented and discussed in the paper 'How to Document Ontology Design Patterns' presented at the Workshop on Ontology and Semantic Web Patterns in conjunction with the International Semantic Web Conference 2016.

The dataset contains two CSV files, each corresponding to one of the two surveys discussed in Section 3 of the paper in question. Both files include the questions (row 1), answer options (row 2), and provided answers (row 3 and onward). OEMS-Data.csv contains the data discussed in Section 3.1 (Table 2/3) and ODPT-Data.csv contains the data discussed in Section 3.2 (Table 4).

The dataset was originally published in DiVA and moved to SND in 2024.

Undersökningsdata presenteras och diskuteras i artikeln "How to Document Ontology Design Patterns" som presenterades vid Workshop on Ontology and Semantic Web Patterns i samband med International Semantic Web Conference 2016.

Datasetet innehåller två CSV-filer, som var och en motsvarar en av de två undersökningar som diskuteras i avsnitt 3 i den aktuella artikeln. Båda filerna innehåller frågorna (rad 1), svarsalternativ (rad 2) och tillhandahållna svar (rad 3 och framåt). OEMS-Data.csv innehåller data som diskuteras i avsnitt 3.1 (tabell 2/3) och ODPT-Data.csv innehåller data som diskuteras i avsnitt 3.2 (tabell 4).

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
How to Document Ontology Design Patterns : Supporting Data Part 2
Keywords: data; data; informatics; informatik; Computer Sciences; Datavetenskap (datalogi)